Health Insurance Disparities among Immigrants: Are Some Legal Immigrants More Vulnerable Than Others? - Pandey, Shanta; Kagotho, Njeri (Health & Social Work, 2010)
This study examined health insurance disparities among recent immigrants. The authors analyzed all working-age adult immigrants between the ages of 18 and 64 using the New Immigrant Survey data collected in 2003. This survey is a cross-sectional interview of recent legal permanent residents on their social, economic, and health status. Respondents were interviewed in English or in their preferred languages. Nearly two-thirds of immigrants were uninsured, in spite of their strong labor force participation. Of the four key classes of immigration-employment based, family sponsored, refugee/asylum program, and diversity program-the diversity program immigrants were least likely to be insured, controlling for a wide array of demographic, human capital, acculturation, and assets-related variables. Strategies to increase health insurance coverage among legal immigrants, especially diversity immigrants, are discussed.